Design and analysis of a high voltage gain DC - DC converter for renewable energy applications - K, Pradeepa; V, Bharkavi; J, Suruthi; M, Priyadharshini (International Journal of Engineering and Technology, 2018)
The project deals with a completely unique high voltage gain, high-efficiency dcâ€“dc device supported coupled inductance, intermediate ca-pacitance, and run energy recovery theme. The input energy nonheritable from the supply is initial keep within the force field of coupled inductance and intermediate capacitance in an exceedingly lossless manner. In different stages, its passed to the output. Victimization MPPT technique, most power is tracked and therefore the most output voltage gain is achieved. By attaining soft change losses may also be cor-rected.Â Â